Effects of Maternal Depression on Adolescent Offspring Depression and Anxiety: Mediating Role of Emotional Trauma in a Community-Based Study - Kim, Jihwan; Joo, Min Ah; Moon, Duk-Soo; Kwack, Young Sook; Kim, Bung-Nyun; Kang, Na Ri (Journal of the Korean Academy of Child and Adolescent Psychiatry, 2025)
Maternal depression negatively affects depression and anxiety symptoms in the offspring. This study examined the association between maternal depression and their adolescent offspring depression and anxiety, as well as the mediating role of emotional trauma in determining the association. Participants were 237 mothers (46.08±5.00 years) and their adolescent offspring (16.54±1.51 years). The participants completed the Beck Depression Inventory-II, Early Trauma Inventory Self Report-Short Form, Center for Epidemiological Studies Depression Scale for Children, and the Screen for Children's Anxiety Related Disorders. The mediating effect of emotional trauma on offspring was explored using mediation analysis. Maternal depressive symptoms were significantly correlated with adolescent offspring traumatic experiences, as well as with their depressive and anxiety symptoms. Mediation analysis results showed that emotional trauma of offspring significantly mediated the effect of maternal depression on their depressive and anxiety symptoms. Findings indicate that maternal depression was significantly associated with depressive and anxiety symptoms in adolescent offspring, mediated by their emotional trauma. Future research is needed to investigate pathways and intervention strategies to prevent the intergenerational transmission of emotional problems.